Aligning Philippine K to 12 assessment policies against international benchmarks implications for quality reform - Lapinid, Minie Rose C. (Philippine Journal of Science, 2024)
This study employs document analysis to examine the alignment between Philippine K-12 assessment policy guidelines and international large-scale assessments (ILSAs). The aim is to benchmark and enhance Philippine assessment standards by identifying ILSA key standard indicators that are well-articulated, require further elaboration, or are missing but could be adopted in the Philippine Department of Education (DepEd) assessment policy guidelines. Four DepEd assessment policy guidelines–classroom assessment, national assessment, system assessment, and interim assessment–alongside ILSA documents were coded and categorized under the Sustainable Development Goals (SDGs)–specifically SDG4 (Quality Education), SDG5 (Gender Equality), and SDG 10 (Reduced Inequality). The coded ILSA key standard indicators were then mapped against those in DepEd documents. The analysis reveals both coherence and gaps between DepEd policies and ILSAs, pointing to the need for more detailed articulation of standards and the adoption of additional ILSA standards in Philippine guidelines. While some alignment in terms of quality, equality, and equitable key assessment standards was noted, areas needing enhancement include [1] defining qualifications for expert consultants, [2] balancing test-item difficulty and classification in assessments, [3] using sample items in ILSAs as exemplars in assessments, and [4] tagging approved items in the item bank with classification details. Recommended ILSA standards for adoption include [1] updating item development frameworks to address current issues and trends, [2] implementing adaptive testing and computer-based test administration, and [3] linking test results with students' backgrounds. These findings underscore the importance of assessments that ensure validity, reliability, fairness, and timeliness while informing policy formulation, reforms, and improved assessment practices.